MORPHOMETRIC ANALYSIS OF SUBMANDIBULAR GLAND PARENCHYMA OF INTACT RATS USING THE METHODS OF MULTIVARIATE STATISTICS - Котик, Т.Л. (World of Medicine and Biology, 2014)
Seromucous cells and excretory ducts of intact rats were investigated using morphometry and multivariate statistics methods. Three clusters of terminal portion cells, which characterize the corresponding phases of secretory cycle, were identified by means of cluster analysis. It was determined that seromucous cells, metric parameters of which vary during the secretory cycle, are moving from cluster into the cluster: from cluster 1 into the 2nd – after a certain amount of primary products accumulation; from 2nd cluster into the 3rd – after a sufficient amount of secret synthesis and maturation; from cluster 3 into 1st – after the secretions evacuation. The described above processes pass smooth and parallel. At the same time, the share of #1 cluster cells (those that excrete secret and absorb the required incoming products) equals to the share of #3 cluster cells (those that are ready to secretions evacuation). This fact indicates that the secretory cycle of studied gland terminal portions is to be functionally stable. The principal component analysis allowed to specify the priority of morphological features of intralobular ducts. It was determined that the lumen area of the granular and striated ducts is the most significant, the height of duct epithelial cells less important, and the height of epithelial cells and intercalated ducts lumen area are the least important. The cluster analysis and principal component analysis can serve as a mean of a better salivary gland parenchyma condition assessment (from the side of functional morphology).